THE IMPORTANCE OF RISK EVALUATION IN THE BUSINESS OPERATIONS OF THE COMPANY FROM THE ASPECT OF TOP MANAGEMENT DECISION-MAKING (Heritage, 2021)
The economy of a country, regardless of the dominant ownership structure that prevails in it, should have developed market institutions through which economic development can be built in accordance with the basic objective function of the company, i.e. the target category of "profit maximization". The economy observed in this way is connected to the observation of the financial position of a large number of heterogeneous companies, because in that way the most important indicators can be presented, such as those that reflect the financial health of a large number of companies at the time of observation. A realistic view of the created value of a company implies the simultaneous creation of a competitive advantage and the evaluation of economic effects in the real observation of the economy of a country, such as, for example, the observation of the economy of the Republic of Serbia.     Top management in the process of overall assessment of the investment of necessary resources for the organization of business in the company tries to see as many factors that affect the projection of cash flows, and then assess the possible chances of making possible modifications to maximize profits.     In this study, the authors analyzed the impact of stochastic risk in creating the real value of a company.    In this regard, there is a key issue related to the management of the company, i.e. there is the issue of managing possible risks, especially when it comes to risk comparisons and new investments that arise in the real business of the company.
Keywords: management, value, assets, risk, financial position